Trasmembrane chemokines CX3CL1 and CXCL16 drive interplay between neurons, microglia and astrocytes to counteract pMCAO and excitotoxic neuronal death - Rosito, Maria; Lauro, Clotilde; Chece, Giuseppina; Porzia, Alessandra; Monaco, Lucia; Mainiero, Fabrizio; Catalano, Myriam; Limatola, Cristina; Trettel, Flavia (Frontiers in Cellular Neuroscience, 2014)
Upon noxious insults, cells of the brain parenchyma activate endogenous self-protective mechanisms to counteract brain damage. Interplay between microglia and astrocytes can be determinant to build a physiological response to noxious stimuli arisen from injury or stress, thus understanding the cross talk between microglia and astrocytes would be helpful to elucidate the role of glial cells in endogenous protective mechanisms and might contribute to the development of new strategy to mobilize such program and reduce brain cell death. Here we demonstrate that chemokines CX3CL1 and CXCL16 are molecular players that synergistically drive cross-talk between neurons, microglia and astrocytes to promote physiological neuroprotective mechanisms that counteract neuronal cell death due to ischemic and excitotoxic insults. In an in vivo model of permanent middle cerebral artery occlusion (pMCAO) we found that exogenous administration of soluble CXCL16 reduces ischemic volume and that, upon pMCAO, endogenous CXCL16 signaling restrains brain damage, being ischemic volume reduced in mice that lack CXCL16 receptor. We demonstrated that CX3CL1, acting on microglia, elicits CXCL16 release from glia and this is important to induce neroprotection since lack of CXCL16 signaling impairs CX3CL1 neuroprotection against both in vitro Glu-excitotoxic insult and pMCAO. Moreover the activity of adenosine receptor A3R and the astrocytic release of CCL2 play also a role in trasmembrane chemokine neuroprotective effect, since their inactivation reduces CX3CL1- and CXCL16 induced neuroprotection.